Achalasia Cardia in a 6-Month-Old Boy: Case Report and Review of Literature (BIRDEM Medical Journal, 2016)
Achalasia cardia is commonly seen in adult population. It is extremely rare in infants and seldom found in children. Diagnosis of the disease is difficult in children particularly in small infants because the typical symptoms are missing and hardly there are any sign.High index of suspicion should be exercised to bring it among the differentials. We have described a 6-month-old boy with achalasia cardia and reviewed recent literatures to elucidate current scenario.Birdem Med J 2016; 6(1): 46-49